2021
DOI: 10.3390/nano11030744
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Silver Nanoparticles on Tobacco Plants: Evaluation of Coating Effects on Photosynthetic Performance and Chloroplast Ultrastructure

Abstract: Silver nanoparticles (AgNPs) are the most exploited nanomaterial in agriculture and food production, and their release into the environment raises concern about their impact on plants. Since AgNPs are prone to biotransformation, various surface coatings are used to enhance their stability, which may modulate AgNP-imposed toxic effects. In this study, the impact of AgNPs stabilized with different coatings (citrate, polyvinylpyrrolidone (PVP), and cetyltrimethylammonium bromide (CTAB)) and AgNO3 on photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…The irregular shape of chloroplasts with protrusions and less stacking of grana was also shown in broad bean seedlings after seed priming with high concentrations of AgNPs [64]. Plastoglobuli increased in number and size in leaf cells and [20] found the same results where leaves of tobacco plants treated with AgNP-PVP and AgNP-CTAB were containing thinner and longer chloroplasts and large plastoglobules compared to the control. These structures may be associated with senescing of chloroplasts [65] play a role in the breakdown of carotenoids and oxidative stress defense [66].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The irregular shape of chloroplasts with protrusions and less stacking of grana was also shown in broad bean seedlings after seed priming with high concentrations of AgNPs [64]. Plastoglobuli increased in number and size in leaf cells and [20] found the same results where leaves of tobacco plants treated with AgNP-PVP and AgNP-CTAB were containing thinner and longer chloroplasts and large plastoglobules compared to the control. These structures may be associated with senescing of chloroplasts [65] play a role in the breakdown of carotenoids and oxidative stress defense [66].…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that AgNPs cause ultrastructural malformation in the cells of different plants such as rice [15], barley [16], Brassica [17], tobacco [18][19][20], and Scots pine and oak [21]. Also, [22] reported obvious changes in the anatomy of the lettuce leaves in response to the Ag NPs compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the AgNPs market was reported to be $1 billion, which is expected to rise to $3 billion by 2024 [ 20 , 21 ]. Due to the antibacterial, antifungal, antiseptic, and antiviral properties, AgNPs are of prime importance in medical applications and were broadly used as an antimicrobial agent before the discovery of antibiotics [ 19 , 22 , 23 ]. Up until now, AgNPs have been utilized in a diverse range of applications in many fields, with some examples of health (immunity-based food supplements, pharmaceuticals, disinfectants, burn treatment products, and wound healing/dressings, radiotherapy), other biomedical products, optics, biosensing, environmental remediation, food industries, cleaning, water and air disinfection, electronics, textile, packaging, skincare products, detergents, plastics, paints, and even children toys [ 21 , 24 , 25 , 26 , 27 ].…”
Section: Applications Of Silver Nanoparticlesmentioning
confidence: 99%
“…AgNP stabilization is usually obtained by either steric stabilization, which arises as a consequence of polymer adsorption onto the surface of particles [ 42 ], or electrostatic stabilization, which includes surface charge development, usually by physical adsorption of charged species onto the surface [ 43 ]. Among nonionic polymer coatings, the most frequently used one is PVP, which has been applied in numerous investigations performed on plants [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and algae [ 14 , 20 , 23 ]. Besides PVP, polyethylene glycol (PEG) and polyvinyl alcohol (PVA) have also been frequently used for AgNP stabilization in both plant [ 52 , 53 , 54 , 55 , 56 , 57 ] and algal research [ 19 , 20 , 26 , 28 ], while GA, a natural polymer consisting of polysaccharides and glycoproteins, has mostly been utilized in plant studies [ 10 , 46 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%